Comparative evaluation of coronally positioned flap with or without using a collagen barrier membrane for root coverage procedures: A clinical study - Anup Cholepati; S.S. Doiphode; Motilal Jangid (Tabriz University of Medical Sciences, 2017)
Gingival recession is defined as displacement of gingival margin apical to cementoenamel junction. Over the years gingival recession has been treated by a number of surgical techniques. Conventional mucogingival procedures such as the laterally positioned flap, free gingival graft, connective tissue graft and coronally positioned flap have been shown to be relatively successful in achieving root coverage. Gingival tissue regeneration (GTR) based root coverage has emerged as an alternative treatment because it demonstrates histologically new attachment formation. The aim of this study was to compare coronally positioned flap procedures in gingival recession defects with or without using a collagen barrier membrane.